Representation of Inferiority and Superiority in the Drama Script Kereta Kencana by W.S. Rendra - Inez Catur Windy Carmitha (Winaya Inspirasi Nusantara Foundation, 2023)
This article aims to describe the form of inferiority of grandfather and grandmother characters in the drama script Kereta Kencana by W.S. Rendra describe the form of superiority of grandfather and grandmother characters in the drama script Kereta Kencana by W.S. Rendra. The method used is descriptive qualitative. The source of data in the study is the play Kereta Kencana by W.S. Rendra. The data was analyzed using the individual psychology approach of Alfred Adler's theory. The results of the research were found in the form of a form of inferiority of Grandfather's character consisting of feelings of pessimism, feelings of sadness, and feelings of frustration, while the form of inferiority of Grandmother's character is a feeling of excessive worry. The form of superiority is only found in Grandmother's character in the form of a creative self-superiority complex.